Immune Modulation of Cardiac Repair and Regeneration: The Art of Mending Broken Hearts - Zlatanova, Ivana; Pinto, Cristina; Silvestre, Jean-Sébastien (Frontiers in Cardiovascular Medicine, 2016)
The accumulation of immune cells is amongst the earliest responses that manifest in the cardiac tissue after injury. Both innate and adaptive immunity coordinate distinct and mutually non-exclusive events governing cardiac repair including elimination of the cellular debris, compensatory growth of the remaining cardiac tissue, activation of resident or circulating precursor cells, quantitative and qualitative modifications of the vascular network and formation of a fibrotic scar. The present review summarizes the mounting evidence suggesting that the inflammatory response also guides the regenerative process following cardiac damage. In particular, recent literature has reinforced the central role of monocytes/macrophages in poising the refreshment of cardiomyocytes in myocardial infarction- or apical resection-induced cardiac insult. Macrophages dictate cardiac myocyte renewal through stimulation of pre-existing cardiomyocyte proliferation and/or neovascularization. Nevertheless, substantial efforts are required to identify the nature of these macrophage-derived factors as well as the molecular mechanisms engendered by the distinct subsets of macrophages pertaining in the cardiac tissue. Among the growing inflammatory intermediaries that have been recognized as essential player in heart regeneration, we will focus on the role of interleukin-6 and interleukin-13. Finally, it is likely that within the mayhem of the injured cardiac tissue, additional types of inflammatory cells, such as neutrophils, will enter the dance to ignite and refresh the broken heart. However, the protective and detrimental inflammatory pathways have been mainly deciphered in animal models. Future research should be focused on understanding the cellular effectors and molecular signals regulating inflammation in human heart to pave the way for the development of factual therapies targeting the inflammatory compartment in cardiac diseases.